Investigation of the effects of femtosecond laser surface texturing on metallic materials - Palaniappan Manickam (2019)
Femtosecond lasers are ultra short pulse lasers that have become highly important in the modern world, as it is being used for a wide range of applications, from scientific experiments to cataract surgery. It emits ultra short pulses (1 fs = 10−15 s) with outstanding precision, which is a key requirement for various applications in different fields of work. Femtosecond laser surface texturing is one such application which provides high precision for the generation of surface functionalities based on the mechanical, chemical and optical properties of a material. However, the effects of laser surface texturing would be different from one material to another. This project primarily focuses on the investigation of the effects of femtosecond laser surface texturing on various metallic materials, which would be determined through a detailed analysis of the microstructures of selected metallic materials. The process of analysis will encompass the selection of three metallic materials of the same thickness and quality, selecting variables for the experiment, set-up of the fiber femtosecond laser system, creating hatch features on the surface of the metallic materials and lastly, the observation and analysis of the micro structure of the created hatch features using an optical microscope. The depth of the micro structures will subsequently be analysed and included in this report. For future analysis, other metallic materials could be tested, and the number of variables could be increased to obtain better results. Further tests may also be done to determine how the properties, such of fatigue and hardness, after affected by the laser surface texturing process.